The Resistance of Local Pigmented Rice Varieties against Bacterial Leaf Blight - Tri Joko; Kristamtini Kristamtini; Sumarno Sumarno; Rofiq Andriyanto (Universitas Gadjah Mada, 2019)
Bacterial leaf blight (BLB) caused by Xanthomonas oryzae pv. oryzae (Xoo) is an important disease in rice plants worldwide, including in Indonesia. The use of resistant variety against BLB is the best effort in disease control because it is considered as the most effective and environmentally friendly. This study aimed to evaluate the resistance of local varieties, red rice (cv. Sembada Merah) and black rice (cv. Sembada Hitam), against Xoo compared to white rice variety (Ciherang), commonly cultivated by the farmers. The study was conducted in a greenhouse and arranged in Factorial of Completely Randomized Design (CRD) with 5 replications and 2 treatment factors: variety (Sembada Hitam, Sembada Merah, and Ciherang) and inoculation (with and without inoculated by Xoo bacterial suspension). Xoo inoculation was performed by clipping the leaves that close to the reproductive phase when the heading begins to be produced. The disease intensity and Area Under Disease Progress Curve (AUDPC) over two weeks were used to determine the level of resistance of the tested plant varieties. The results showed that black rice and red rice had better levels of resistance against BLB compared to white rice. At two weeks after inoculation, Sembada Hitam had the lowest AUDPC value followed by Sembada Merah, while the Ciherang had the highest AUDPC value and was categorized as a susceptible variety to Xoo.